Necroptosis pathways in tumorigenesis. (November 2022) - Zhang, Tao; Wang, Yingnan; Inuzuka, Hiroyuki; Wei, Wenyi
Abstract: Necroptosis is a caspase-independent form of programmed cell death executed by the receptor interacting protein kinase 1 (RIPK1)-RIPK3-mixed lineage kinase domain-like protein (MLKL) signaling cascade, deregulation of which can cause various human diseases including cancer. Escape from programmed cell death is a hallmark of cancer, leading to uncontrolled growth and drug resistance. Therefore, it is crucial to further understand whether necroptosis plays a key role in therapeutic resistance. In this review, we summarize the recent findings of the link between necroptosis and cancer, and discuss that targeting necroptosis is a new strategy to overcome apoptosis resistance in tumor therapy.